Human Age Estimation Through DNA Metilation Analysis Method from Bite Mark Samples in Forensic Identification - Ahmad Yudianto1 , Mieke Sylvia Margaretta AR2 , Fery Setiawan3 , Ma’rifatul Ula4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Age estimation are often calculated using bone and teeth samples, but are limited to humanskeleton findings. The aim of this research is to estimate human age through DNA methylation methodfrom bite mark samples. Result: There were 40 bite mark samples obtained from healthy volunteers. DNAsamples were isolated using DNAzol reagent and converted using DNA methylation kit. The isolated DNAwere amplified and electrophoreses was conducted using agarose gel. Electrophoresis result was used aslength reference for the sequenced band and analyzed for methylation percentage and correlation withage estimation. Statistical test showed that there was a significant correlation between DNA methylationpercentage with age estimation both in men (r Pearson 0.767) and women (r Pearson 0.878). Conclusion:Cpgplot emboss analysis for DNA methylation mean percentage in men tend to increase in accordance toage categories, whereas for women, the mean DNA methylation percentage in age categories was stable orconstant.